Platelets collection by apheresis, performance and effect of variables of donors in the process - Zumbado Salas, Greyvin (2015)
A retrospective study using records of aphaeresis platelet donors at the blood bank of the Hospital Mexico donations between 2011 and 2014, to evaluate the performance and characteristics of the donors which may influence this quality and efficiency of platelets concentrate collections. A total of 1 480 plateletpheresis collections were performed to 501 donors, 242 were a single product collection, 1013 were a double the product collection and 225 triple the product was collected, 34.9% of donors were female and 65.1% male donors. In the programmed collection procedures for single product (2.5X1011), double product (5x10n) and triples (7.5x10n) the real yields obtained were 3.04x10n, 5.12x10n and 7.73x10n in respective order. States that selecting donors over 220 x103 platelets and more than 60 kg weight were able to make the donation of double product in less than 69 minutes and if these parameters increase to 305 x103 platelets and 65 kg per donor, 94% of donors may make donations of triple product in less than 69 minutes so reducing the cost-effectiveness ratio of platelets donation using aphaeresis, without any additional risk and obtaining product of excellent yield ratio and quality.